Nausea and Vomiting during the First 3 Intercycle Periods in Chemo-naive Cancer Patients Receiving Moderately/Highly Emetogenic Therapy. Issue 6 (November 2015) - Pessi, Maria Adelaide; Necchi, Andrea; Bossi, Paolo; Resteghini, Carlo; Giannatempo, Patrizia; Ferrari, Laura; Zilembo, Nicoletta; Ripamonti, Carla Ida
Aims and Background: There is a paucity of data regarding the incidence, intensity, and treatment of nausea and vomiting during the intercycle periods of chemotherapy (CHT). The aims of the study were to assess the incidence and intensity of intercycle nausea and vomiting, to assess the use of rescue antiemetic medications, and to define the more uncomfortable symptom between nausea and vomiting. Methods: In a prospective study, 108 chemotherapy-naive patients treated with highly or moderately emetogenic CHT for different primary cancers were enrolled. All patients filled out the Edmonton Symptom Assessment System tool before the first cycle of CHT (T0) and on 14-16 days thereafter for the first 3 cycles of CHT (i.e., T1, T2, T3). Results: Sixty-seven patients completed the study. During CHT administration, all patients received antiemetics according to international guidelines. During the intercycle periods, nausea was reported in 6.0% of patients at T0, 10.5% at T1, and 26.9% at T2 and T3, respectively. The intensity of nausea was mild for 6.0%, 21%, and 18% of patients at T1, T2, and T3, respectively; moderate for 1.5%, 3.0%, and 6.0% at T1 to T3; and severe in only 3.0% of patients at any time. Vomiting was present in 1.5% and 10.5% of patients at T2 and T3. Rescue antiemetic medication was required for 41.8% at T1, 53% at T2, and 47.8% at T3. At the end of the study, 70.1% of patients described nausea as the more uncomfortable symptom compared to vomiting. Conclusions: Nausea has a higher burden of impact over vomiting and should be assessed and treated separately throughout multiple cycles of CHT.